Advances in α-C(sp3)–H functionalization of ethers via cascade [1, n]-hydride transfer/cyclization. (19th November 2022) - Shen, Yao-Bin; Hu, Fangzhi; Li, Shuai-Shuai
Abstract: The α -C(sp 3 )–H functionalization of ethers via cascade [1, n]-hydride transfer/cyclization, which features redox-neutral nature, atom-economy, and high efficiency in the assembly of O -containing heterocycles, constitutes an attractive yet challenging research topic in organic synthesis. This comprehensive review highlights the impressive advances made in this realm during the past two decades, and the content is classified, for clarity, by the types of α -C(sp 3 )–H functionalization using different hydride acceptors. The proposed mechanisms, characteristics, limitations and directions in the future are presented as well. Graphical abstract: Image 1